Mechanistic Insights into Phenol Oxidation by a Copper(II) Complex of a Pyridine‐ and Amide‐Containing Copolymer in an Aqueous Medium. Issue 3 (January 2015) - Lykourinou, Vasiliki; Ming, Li‐June
Abstract: Invited for the cover of this issue is the group of Li‐June Ming at the University of South Florida, USA. The cover image shows the pathways for phenol oxidation by copper(II) centers of a copolymer scaffold in an aqueous environment, representing a green method for chemical processes and environmental remediation. Abstract : The easy preparation of the metallopolymers and their potential in various metal‐mediated catalysis reactions will allow us to explore broad applications... Read more about the story behind the cover in the Cover Profile and about the research itself onp. 375 ff .